2022
DOI: 10.1016/j.jaci.2021.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell characterization of dog allergen–specific T cells reveals TH2 heterogeneity in allergic individuals

Abstract: Background: Allergen-specific type 2 CD4 1 T H 2 cells are critically involved in the pathogenesis of IgE-mediated allergic diseases. However, the heterogeneity of the T H 2 response has only recently been appreciated. Objective: We sought to characterize at the single-cell level the ex vivo phenotype, transcriptomic profile, and T-cell receptor (TCR) repertoire of circulating CD4 1 T cells specific to the major dog allergens Can f 1, Can f 4, and Can f 5 in subjects with and without dog allergy. Methods: Dog … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…In the meantime, Morgan et al found that Th2A cells are enriched in esophageal tissue from EoE patients and associated with the recruitment of eosinophils to the esophageal tissue, indicating that Th2A cells are the pathogenic cells for EoE (38). A recent study by Vandamme et al using TCR and transcriptomic analysis of dog allergen-specific T cell responses in allergic subjects revealed a close relationship between Th2-like, Th2, and Th2A cells (39).…”
Section: Discovery Of Th2a Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, Morgan et al found that Th2A cells are enriched in esophageal tissue from EoE patients and associated with the recruitment of eosinophils to the esophageal tissue, indicating that Th2A cells are the pathogenic cells for EoE (38). A recent study by Vandamme et al using TCR and transcriptomic analysis of dog allergen-specific T cell responses in allergic subjects revealed a close relationship between Th2-like, Th2, and Th2A cells (39).…”
Section: Discovery Of Th2a Cellsmentioning
confidence: 99%
“…A recent study by Vandamme et al. using TCR and transcriptomic analysis of dog allergen–specific T cell responses in allergic subjects revealed a close relationship between Th2-like, Th2, and Th2A cells ( 39 ).…”
Section: Discovery Of Th2a Cellsmentioning
confidence: 99%
“…These cells have been coined Th2A cells [34]. These allergen‐reactive Th2‐biased Th cells with increased pathogenicity and terminal differentiation as well as reduced clonality can also be identified in individuals with allergies, as recently shown for dog allergen‐reactive T cells by single‐cell RNA sequencing [35].…”
Section: Th Cell Regulation Revisitedmentioning
confidence: 99%
“…In 2017, Wambre et al identified Th2a cells, which express a terminally differentiated CD4 + memory phenotype characterized by CD161+CD27-CrTh2+CD49d+ expression and appear to carry the Th2 memory cell function over a long time [18][19][20]. On allergen stimulation, these Th2a cells secrete high amounts of IL-4, IL-13, IL-9, and IL-5 [18], which can be further increased by epithelium-derived IL-33 [21].…”
Section: Th2a Cellsmentioning
confidence: 99%